Coinfection of High-Risk and Low-Risk Human Papillomavirus in Urethra Condylomata Accuminata - Lita Setyowatie; Noor Hidayah (Faculty of Medicine, Universitas Airlangga, 2020)
Background: Condylomata accuminata (CA) is a sexually transmitted infection caused by the Human Papillomavirus (HPV), which has more than 40 subtypes classified into high and low risks. The incidence of coinfection involving HPVs in genitalia varies between 2%–71%. Coinfection events increase in immunosuppressed patients. Purpose: To know the types of HPV in CA lesions and the risk factors of a high and low-risk HPV coinfection. Case: A 45-year-old woman presented with genital warts appeared three weeks before. The patient had a breast cancer history and undergone chemotherapy. The examination revealed multiple papules with verrucous surface, firm borders, with whitish color around the urethra and on the vaginal wall. Acetowhite test was positive. The biopsy examination showed squamous epithelium arranged to form papils and foci suspected as koilocytes suggesting CA. The Human Immunodeficiency Virus (HIV) rapid test, VDRL (Venereal Disease Research Laboratory) and TPHA (Treponema Pallidum Haemagglutination) examinations showed non-reactive results. The HPV deoxyribonucleic acid (DNA) genotyping test showed positive results for HPV type 56 (High-Risk Genotypes) and HPV type 6 (Low-Risk Genotypes). She was treated with electrosurgery and consulted to the urology department. Discussion: Coinfection of HPVs might cause a persistent HPV infection for a longer duration, as well as the risk of developing into cancerous lesion. The mechanism of high-risk and low-risk HPV coinfection in immunosuppressed individuals might be due to faster replication of the virus or reactivation of a latent infection. Conclusion: Coinfection of 2 types of HPV could happen in immunosuppression condition such as in patient undergone chemotherapy.